Activation of transient receptor potential vanilloid 3 is required for keratinocyte differentiation and epidermal barrier formation - Chung, Elina Da Sol; Nam, Yu Ran; Kim, Hyun Jong; Jeon, Young Keul; Park, Kyung Sun; Kim, Woo Kyung; Kim, Sung Joon; Nam, Joo Hyun (The Korean journal of physiology & pharmacology, 2025)
Transient receptor potential vanilloid 3 (TRPV3)-mediated Ca² signaling in keratinocytes plays a crucial role in epidermal keratinocyte differentiation and triggers the release of pro-inflammatory cytokines, causing inflammation and itching. However, the regulation of skin barrier recovery by TRPV3 and its expression during keratinocyte differentiation remain unexplored. This study aimed to investigate the role and expression levels of TRPV3 in keratinocyte differentiation and skin barrier recovery, focusing on the effects of varying TRPV3 activation using pharmacological agents. Differentiation of primary human keratinocytes was induced in high-calcium media, and TRPV3 activity and expression were assessed using patch-clamp, fura-2 fluorimetry, and immunoblotting. The effects of TRPV3 agonists on skin barrier recovery following tape stripping were evaluated by measuring transepidermal water loss in mice. Results showed that TRPV3 expression, current density, and agonist-induced [Ca ] changes increased with keratinocyte differentiation. The TRPV3 antagonist, ruthenium red, inhibited both keratinocyte differentiation and TRPV3 upregulation. TRPV3 agonists (2-APB/carvacrol) facilitated early differentiation but paradoxically downregulated TRPV3 expression at higher concentrations. Moderate TRPV3 activation by lower agonist concentrations enhanced skin barrier recovery, while higher concentrations hindered recovery and induced immune cell infiltration. These findings highlight the dual role of TRPV3 in skin homeostasis and suggest that targeted modulation of TRPV3 could be a promising strategy for treating skin disorders.